Immunolocalization of bone morphogenetic protein 2 during the early healing events after guided bone regeneration - De Marco, Andrea Carvalho; Jardini, Maria Aparecida Neves [UNESP]; Modolo, Filipe; Nunes, Fabio Daumas; Alves de Lima, Luiz Antonio Pugliesi (Elsevier B.V., 2012)
Objective. The objective of this study was to evaluate the immunolocalization of bone morphogenetic protein 2 (BMP-2) after autogenous block grafting covered or not with an e-PTFE membrane.Study Design. Forty-eight rats were divided into 2 groups, autogenous block graft (B) and autogenous block graft + e-PTFE membrane (MB), and were evaluated by immunohistochemistry at baseline and 3, 7, 14, 21, and 45 days.Results. The largest number of positive cells in the recipient bed was observed after 3 days in both groups. At the graft border, the largest number of positive cells was seen after 7 days in group B and after 14 days in group MB. The highest proportion of staining in the graft was observed after 3 days in group B and after 21 days in group MB.Conclusions. High proportions of stain were related to intense revascularization and osteogenesis. Except for the interface, BMP-2 staining occurred later in group MB than in group B in all structures analyzed. (Oral Surg Oral Med Oral Pathol Oral Radiol 2012;113:533-541)